Internalisasi Nilai Karakter Disiplin pada Siswa Sekolah Dasar - Putri Arini Hidayati Putri; Cahyani dwi puspitasari cahyani; Agung Setyawan Agung setyawan (Bildung: Jurnal Ilmu Pendidikan, 2026)
Character education in discipline among elementary school students plays a strategic role in shaping attitudes of responsibility, orderliness, and independence from an early age. However, various findings in the field indicate that the implementation of disciplinary values in elementary schools is still not optimal and tends to be normative. This study aims to describe the process of internalizing the character value of discipline in elementary school students through a literature review using a qualitative descriptive approach. Discipline as an essential character value plays an important role in shaping students' responsibility, orderliness, and independence. However, the phenomenon in the field shows that the implementation of the value of discipline in elementary schools is still weak. This study uses data sources obtained from sixteen accredited national scientific journals published between 2015–2025. The results of the analysis indicate that the internalization of the character value of discipline can be done through habituation in routine school activities, teacher role models, strengthening school culture, and integration in thematic and religious learning. The main supporting factors include the role of teachers, parental support, and a conducive school climate. Meanwhile, the inhibiting factors are low student awareness and weak supervision in the implementation of discipline. This study confirms that the internalization of the character value of discipline in elementary schools needs to be carried out sustainably through synergy between schools, families, and communities to shape the character of responsible and integrity students.